2021
DOI: 10.46977/apjmt.2021v02i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Daylight Illumination and Building Architecture - Effect at Workplace

Abstract: Occupational health and architecture on the modern office-based work environment is a major public health concern of this era. Information and communication technology have created a world where a high-quality working environment is vital for the office workers. Majority of the nation provide quantity rather than quality of work conditions. According to the researcher's poor indoor environmental quality, such as illumination, has a detrimental influence on human health and performance. The purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Hormon melatonin biasa disebut juga dengan sleep hormon, sedangkan kortisol merupakan hormon stres yang meningkat di pagi hari. Cahaya dibutuhkan tubuh untuk menghasilkan hormon sesuai dengan jam kerja untuk menghindari kurangnya konsentrasi dan resiko kecelakaan kerja [2,15]. Kinerja pencahayaan dalam suatu ruangan dapat dikatakan baik apabila cahaya matahari masuk ke dalam ruangan secara optimal pada pukul 08.00 hingga 16.00 dengan distribusi cahaya yang merata atau tidak ada kontras antara bagian yang terang dan gelap.…”
Section: Landasan Teoriunclassified
“…Hormon melatonin biasa disebut juga dengan sleep hormon, sedangkan kortisol merupakan hormon stres yang meningkat di pagi hari. Cahaya dibutuhkan tubuh untuk menghasilkan hormon sesuai dengan jam kerja untuk menghindari kurangnya konsentrasi dan resiko kecelakaan kerja [2,15]. Kinerja pencahayaan dalam suatu ruangan dapat dikatakan baik apabila cahaya matahari masuk ke dalam ruangan secara optimal pada pukul 08.00 hingga 16.00 dengan distribusi cahaya yang merata atau tidak ada kontras antara bagian yang terang dan gelap.…”
Section: Landasan Teoriunclassified
“…This is a progressive area for the applied sciences. Another research found that day light illumination plays an important role in employee health and thereby adversely affects work productivity (Poddar & Guha, 2021). To understand ergonomics better, the population and its need for compensating biological appliances, as well as the responses regarding those alterations, need to be studied.…”
Section: Introductionmentioning
confidence: 99%